Yard Crane Rescheduling in Uncertain Situations - Nguyen, Văn Hùng; Nguyen, Vũ Anh Duy; Nguyen, Hữu Thọ; Nguyen, Lê Thái; Nguyen, Thanh Tân (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
The container transportation is the most important mode of transportation around the world. This paper considers the scheduling and rescheduling of yard cranes. These cranes are the most important equipment in the container terminals. They influent the terminal’s throughput efficiency. The makespan is the criteria for validation of solutions. Two rescheduling strategies were considered and demonstrated through numerical examples. A lower bound is used to compare the results.